Location, Location, Location: Effects of Cross-Religious Primes on Prosocial Behavior. Issue 4 (1st October 2016) - Xygalatas, Dimitris; Klocová, Eva Kundtová; Cigán, Jakub; Kundt, Radek; Maňo, Peter; Kotherová, Silvie; Mitkidis, Panagiotis; Wallot, Sebastian; Kanovsky, Martin
ABSTRACT: Priming with religious concepts is known to have a positive effect on prosocial behavior; however, the effects of religious primes associated with outgroups remain unknown. To explore this, we conducted a field experiment in a multicultural, multireligious setting (the island of Mauritius). Our design used naturally occurring, ecologically relevant contextual primes pertinent to everyday religious and secular life while maintaining full experimental control. We found that both ingroup and outgroup religious contexts increased generosity as measured by a donation task. In accordance with previous research, we also found an interaction between individual religiosity and the efficacy of the religious primes. We discuss these findings and their interpretation, and we suggest potential avenues for further research.